(untitled) (Journal of the College of Basic Education, 2022)
The study included the collection of 390 gland toxicity of the Red Wasp Vespa orientalis (P1) and 418 gland toxicity of yellow wasp Polistes olivaceaus (P2) from different area of Baghdad city were it classified depend on taxonomic keys in order to diagnose and identify the general characteristics of each species, and then extract gland toxicity to get poison. The results refer to found a relationship between the influence of the wasp type and dose on the red blood cells lysis degree in males and females, it was observed that the concentration had a significant effect (p<0.05) in the red blood cells lysis degree in females, it was 0.401 at concentration 100% for wasp red toxin P1, while it was 0.331 at the same concentrate for wasp yellow toxin P2, the concentration also had a significant effect (p<0.05) in the red blood cells lysis degree in males, it was 1.020 at concentration 100% for wasp red toxin P1, while it 0.842 at the same concentrate for wasp yellow toxin P2, also it refer to found a significant effect (p<0.05) between the effect of the wasp red P1 and yellow P2 toxin and dose on the red blood cells clotting time in females, it was 46.80 min at concentration 100% for wasp red toxin P1, while it was 46.20 min at the same concentrate for wasp yellow toxin P2, the concentration also had a significant effect (p<0.05) in the red blood cells clotting time in males, it was 47.80 min at concentration 100% for wasp red toxin P1, while it 40.47 min at the same concentrate for wasp yellow toxin P2, there was no significant effects for blood clotting time when making a comparison between the wasp red P1 and yellow P2 toxin for each concentration in females and males. The compared between red blood cells clotting time due the wasp red P1 and yellow P2 toxin dose in females and males did not refer to found a significant effect (p<0.05), the clotting time for wasp red P1 was 46.80 and 47.80 min at concentration 100% for females and males respectively, while the clotting time at concentration 6.25% was 17.30 and 17.10 min for females and males respectively, whilst the clotting time red blood cells due wasp yellow P2 toxin in females was 46.20 min and 47.40 min in males at concentration 100%, and it was 17.00 min in females and 17.10 min in males at concentration 6.25%.